Application of Education Management Information System in the Learning Process at SMP Muhammadiyah Weleri - Dwi Puji Rahayu; Dian Hidayati (International Journal of Social Service and Research, 2023)
Researchers choose the type of qualitative research. To obtain data the author made observations, interviews, documentation, and data validity, namely triangulation. The results of this study include: (1). The implementation of the management information system at SMP Muhammadiyah Weleri has been well implemented which uses data management applications, namely deposits and information technology in supporting the learning process of providing educational services by facilitating learning practices using technological infrastructure, such as learning facilities by integrating computers with wifi. (2). The implementation of the learning process at SMP Muhammadiyah Weleri is before carrying out the learning process must go through three stages, namely the first planning stage. At this stage make an effective day analysis and learning program analysis, make an annual program, compile a syllabus, compile lesson plans, and make learning assessments. Secondly, the implementation stage. At this stage what needs to be done is the aspect of approach in learning, aspects of strategy and tactics in learning, and aspects of methods and techniques in learning. Learning media used in the learning process are print media (books), images, LCDs, and computers. Third, is the evaluation stage. At this stage, it is evaluated, namely learning knowledge that is tested by writing, oral, and exam question lists. Learning evaluation skills are evaluated by practice exams, and task analysis is evaluated by educators themselves. And the form of the test given to the student must remain within the standard of requirements. (3). Factors that support the existence of a management information system are the existence of a despotic system that collects data on educator data and student data. So it can be concluded that management information systems are very supportive in the world of education, especially in the learning process in junior high school.